2017
DOI: 10.1016/j.ccell.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

FTO Plays an Oncogenic Role in Acute Myeloid Leukemia as a N 6 -Methyladenosine RNA Demethylase

Abstract: SUMMARY N6-methyladenosine (m6A) represents the most prevalent internal modification in mammalian mRNAs. Despite its functional importance in various fundamental bioprocesses, the studies of m6A in cancer have been limited. Here we show that FTO, as an m6A demethylase, plays a critical oncogenic role in acute myeloid leukemia (AML). FTO is highly expressed in AMLs with t(11q23)/MLL-rearrangements, t(15;17)/PML-RARA, FLT3-ITD and/or NPM1 mutations. FTO enhances leukemic oncogene-mediated cell transformation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
1,157
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 1,188 publications
(1,235 citation statements)
references
References 73 publications
(106 reference statements)
40
1,157
5
3
Order By: Relevance
“…In this study, Li et al. illustrated that FTO was significantly up‐regulated in certain sub‐types of AMLs such as MLL‐rearranged AML and acute promyelocytic leukaemia 61. Notable enrichment of FTO directly up‐regulated by the oncogenic proteins ( e.g .…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Li et al. illustrated that FTO was significantly up‐regulated in certain sub‐types of AMLs such as MLL‐rearranged AML and acute promyelocytic leukaemia 61. Notable enrichment of FTO directly up‐regulated by the oncogenic proteins ( e.g .…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 99%
“…Mechanistically, FTO exerted its oncogenic role by targeting the tumour suppressor ASB2 and RARA with its m 6 A demethylase catalytic activity. Thus, the FTO‐mediated inhibition of the ASB2/RARA axis with decreased overall m 6 A level markedly contributed to the carcinogenesis of AMLs 61. Recently, researchers have found the antileukaemic activity of R‐2HG, which was the production of mutant isocitrate dehydrogenase 1/2 and used to be considered as an oncometabolite, and FTO was involved in this progress.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 99%
“…In the early 1970s, scientists first showed that mRNA was chemically modified by using radio isotope labelling of m 6 A. But because those studies enriched the mRNA transcripts by selecting their 3ʹ ends, which contain strings of adenosines, researchers worried that those preparations might contain trace amounts of other classes of RNA molecules, as well.…”
Section: Mapping With Antibodiesmentioning
confidence: 99%
“…But because those studies enriched the mRNA transcripts by selecting their 3ʹ ends, which contain strings of adenosines, researchers worried that those preparations might contain trace amounts of other classes of RNA molecules, as well. "People stopped working on this because it was so difficult to get clear insights into whether the m 6 A in mRNA was a contaminant, " says Samie Jaffrey, a chemical biologist at Weill Cornell Medical College.…”
Section: Mapping With Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation